DAKWAH DI TURKI PADA MASA DINASTI UTSMANI - Desi Syafriani; Doni Nofra (Tamaddun, 2018)
The Ottoman dynasty was a dynasty that was quite involved in the development and spread of Islam in Asia, Africa and Europe. The Ottoman dynasty emerged in Turkey when the Islamic world suffered a setback, namely the second period of the Abbasid dynasty, estimated in the 9th century AD. In the development of da'wah in Turkey, the strategy used is not to force in da'wah and to show an attitude of tolerance, through this da'wah strategy in Turkey can run well. In addition to this strategy we must know about the character and character of the Turkish people, namely discipline and obedience to the rules in force. Da'wah activities and developments in Turkey are supported by Catholicism. During his time, Dakwan's activities during the Ottoman period were able to bring Islam to various parts of the Balkan countries such as Bosni, Serbia and Crete.